A Cross-Sectional Study: Pattern of Injuries in Non Fatal Road Traffic Accident Cases - Vijayamahantesh, S.N.; V, Vijayanath (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Background: A cross-sectional study of pattern of injuries in road traffic accidents was conducted over a period of one year involving 179 victims. Material and methods: Males (143) were more commonly involved than females (36) and majority of the victims (56) were in the age group of 21-30 years. Results: Rural victims(151) outnumbered the urban (28). One third of the victims were illiterates. 36 accidents took place in an interval of 2-4PM. Two wheeler occupants (71) were commonly involved than other vehicles and collision between two wheelers and between two wheeler and four wheeler was most common mode of accident. Conclusion: The head and neck region showed more number of fractures and other injuries compared to other body parts and in the limbs right side limbs show more injuries than left side limbs.